2010
DOI: 10.1002/cncr.25229
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of colorectal cancer screening among men screened for prostate cancer

Abstract: BACKGROUND Evidence suggests that colorectal cancer (CRC) screening reduces disease-specific mortality, whereas the utility of prostate cancer screening remains uncertain. However, adherence rates for prostate cancer screening and CRC screening are very similar, with population-based studies showing that approximately 50% of eligible US men are adherent to both tests. Among men scheduled to participate in a free prostate cancer screening program, the authors assessed the rates and correlates of CRC screening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
2
4
0
Order By: Relevance
“…A similar association was found by this group with mammography18 and in an analysis of updated data by Wong and Coups 15. Our data are most readily compared with those recently published by Red et al24 In their multivariate analysis of 331 adult men (60% African American) undergoing free prostate cancer screening through a clinic at Georgetown Medical Center, these investigators did not find race to be predictive of CRC screening compliance, but, similar to the analyses of the BRFSS by Carlos et al, found prostate cancer screening, health insurance, and having a regular primary care provider to be predictive of both ever having had and adherence to colorectal cancer screening. Of note, although similar in racial composition to our cohort, the participants in the Georgetown study are different from those examined in our research, as our population enrolls in the Prostate Cancer Risk Assessment Program for education, clinical surveillance, and research participation relative to prostate cancer risk assessment.…”
Section: Discussionsupporting
confidence: 90%
“…A similar association was found by this group with mammography18 and in an analysis of updated data by Wong and Coups 15. Our data are most readily compared with those recently published by Red et al24 In their multivariate analysis of 331 adult men (60% African American) undergoing free prostate cancer screening through a clinic at Georgetown Medical Center, these investigators did not find race to be predictive of CRC screening compliance, but, similar to the analyses of the BRFSS by Carlos et al, found prostate cancer screening, health insurance, and having a regular primary care provider to be predictive of both ever having had and adherence to colorectal cancer screening. Of note, although similar in racial composition to our cohort, the participants in the Georgetown study are different from those examined in our research, as our population enrolls in the Prostate Cancer Risk Assessment Program for education, clinical surveillance, and research participation relative to prostate cancer risk assessment.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported with patients 65 years and under significantly less likely to undergo CRC screening [2] [3]. The association between no prior history of other cancer screening and low CRC screening has been reported in prior literature [7] [15]. One study reported that individuals who attributed embarrassment and discomfort to breast or prostate cancer screening were significantly less likely to undergo CRC screening [11].…”
Section: Discussionsupporting
confidence: 81%
“…smoking, obesity, etc.) [2] [7] [13]- [16]. Of all these factors, SES is a particularly important social determinant, accounting for up to 62% in the variance of CRC screening participation rates [9].…”
Section: Introductionmentioning
confidence: 99%
“…The populations perceived by health service providers and community members to have low cancer screening participation in Ontario were similar to other studies and included: the uninsured [ 11 , 18 , 20 ], sexual abuse survivors [ 42 - 47 ], people living in crisis, immigrants [ 11 - 17 ], and men [ 5 ]. There was substantial screening heterogeneity within each of these groups, from never-screened to under-screened for all eligible cancers; to up-to-date on some cancer screens but not all eligible screens; to fully screened for all eligible cancers.…”
Section: Discussionmentioning
confidence: 99%